PEMBUATAN APLIKASI TRANSAKSI SISTEM ANTRIAN PELANGGAN PERUSAHAAN LISTRIK NEGARA (PLN) (STUDI KASUS PADA KANTOR PLN PONDOK UNGU PERMAI) - Eka Budhy Prasetya (Tekinfo: Jurnal Bidang Teknik Industri dan Teknik Informatika, 2020)
Queue of customers in PLN are common. This is because the number of customers coming for more than the existing number of cashiers and customer inter-arrival time is shorter than the time it takes the cashier to serve the customers to complete transactions. The result is complete customer wait time for the longer will be served so as to make the customer feel bored. For applications that need to be made of a queue management system that can be used to handle problems that occur queue in order to improve customer satisfaction. Queuing situation in PLN modeled using queuing models Single Phase Multi Channel where more than one cash register and customers waited in the queue line. The maximum number of counters that can be run in the application queue management system as much as 9 counters. Customer queue management system application in the PLN PLN can assist in addressing problems that occur queue segaligus improve service quality to customer satisfaction. UML (United Modeling Language) is a tool used to develop a computer monitoring system and its applications. Keywords: Customer Queue, Application Transaction, UML (United Modeling Language), Multi channel single phase.